Rancangan Balanced Scorecard Sebagai Alat Eksekusi Strategi Pada Perguruan Tinggi Swasta X di Surabaya - Mar’a Elthaf Ilahiyah (EBBANK, 2017)
Application of the Balanced Scorecard concept has been adopted by many companies and even government organizations as has been proposed by Butler, Letza and Neale (1997) in which some of the major organizations in the United States such as the United States Government, Intel, Apple, Miliken. Along with the development of the Balanced Scorecard method is not only used as a performance measurement tool for the business sphere but also serves as a tool for measuring the performance of government organizations and non-profit organizations, including educational organizations. This study uses on of the privat Colleges in Surabaya (PTS X) as the research object. The reason d PTS.X as the object of this study because PTS.X has experienced a drastic decrease the number of students and PTS. X has some major problems were the cause of the need for a review of strategy and planning strategies using the Balanced Scorecard. There are some major problems of PTS. X is as follows: (1) There accepted students. (3) It is not yet optimal work of faculty research and community service. (4) Lack of funding / budget development. Sources of funding, during which only rely on the SPP and DPP student may not dipetahankan again. A qualitative approach with eksploratorif case study method used in this study. Some of the steps in the design process research Balanced Scorecard at PTS. X, among others: (1) Perform translation PTS's vision and mission. X into a number of strategic objectives (2) To measure the performance of each strategic goal. (3) Establish strategic initiatives that should be do by PTS. X. PTS.X strategy has resulted in 13 strategic objectives in the four perspectives of the Balanced Scorecard and 79 of KPI to be used as a measure in the scorecard. Total size is given in the internal process perspective by 50% to satisfy customers and perspectives growth and learning as much as 30%